The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1074/jbc.ra120.013990
|View full text |Cite
|
Sign up to set email alerts
|

AMPKβ1 and AMPKβ2 define an isoform-specific gene signature in human pluripotent stem cells, differentially mediating cardiac lineage specification

Abstract: AMP-activated protein kinase (AMPK) is a key regulator of energy metabolism that phosphorylates a wide range of proteins in order to maintain cellular homeostasis. AMPK consists of three subunits: α, β and γ. AMPKα and β are encoded by two genes, the γ subunit by three genes, all of which being expressed in a tissue-specific manner. If individual isoforms have different functions is not understood so far. Using RNA-Seq technology, we provide evidence that the loss of AMPKβ1 and AMPKβ2 lead to different gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…JMJD3 may be involved in the determination of the cardiomyogenic lineage from mouse ESCs and enhanced the expression levels of Jmjd3, Jmjd2a, and Jhdm1d [ 66 ]. The transcription factor insulin gene enhancer-binding protein 1 (ISL1) plays a key role in cardiac lineage differentiation [ 67 ]. It has been found that ISL1 cooperates with JMJD3 to alter the cardiac epigenome and regulate cardiac differentiation of ESCs [ 65 ].…”
Section: Jmjd3 Function In Embryonic Stem Cellsmentioning
confidence: 99%
“…JMJD3 may be involved in the determination of the cardiomyogenic lineage from mouse ESCs and enhanced the expression levels of Jmjd3, Jmjd2a, and Jhdm1d [ 66 ]. The transcription factor insulin gene enhancer-binding protein 1 (ISL1) plays a key role in cardiac lineage differentiation [ 67 ]. It has been found that ISL1 cooperates with JMJD3 to alter the cardiac epigenome and regulate cardiac differentiation of ESCs [ 65 ].…”
Section: Jmjd3 Function In Embryonic Stem Cellsmentioning
confidence: 99%